Stabilizing Zn Anode Interface by Simultaneously Manipulating the Thermodynamics of Zn Nucleation and Overpotential of Hydrogen Evolution (Adv. Funct. Mater. 48/2022). (25th November 2022) - Wang, Huibo; Li, Heng; Tang, Yuxin; Xu, Zhu; Wang, Kexuan; Li, Qingyuan; He, Bingchen; Liu, Yi; Ge, Mingzheng; Chen, Shi; Hao, Tianwei; Xing, Guichuan; et al.
Abstract : Highly Reversible Zinc Anode In article number 2207898, Yanyan Zhang, Guichuan Xing, Yuxin Tang and co‐workers construct a stable solid‐electrolyte‐interface (SEI) layer to modulate the Zn nucleation and overpotential of hydrogen evolution via introducing the sericin molecular. This SEI layer can thermodynamically stabilize the Zn/electrolyte interface, homogenize the ionic fluxing, and inhibit the hydrogen generation, contributing to the highly reversible zinc anode and the improved electrochemical performance of zinc‐ion batteries.